PENGARUH STRATEGI KUALITAS PRODUK, KEMASAN, DAN KUALITAS PELAYANAN TERHADAP KEPUTUSAN PEMBELIAN DI PT. SURYA ANDALAN GLOBAL ABADI - Leo Nardo Leo Nardo; Jhon Amdiray Saragih; Nurlince Fransiska Simanjuntak Simanjuntak; Hanna Kristin Ravela Ravela; Muhammad Agung Anggoro Anggoro (Jurnal Ekonomi Bisnis Manajemen Prima, 2022)
The research objective was to examine and ianalyze the effect of product quality strategies, packaging and service quality on purchasing decisions at PT. Surya Andalan Global Abadi. Researchers conducted research at PT. Surya Andalan Global Abadi which is located at Pulau Karimun street II, KIM 2, Saentis Village, Percut Sei Tuan District, Deli Serdang Regency, North Sumatra. Researchers plan research activities in September 2020 - August 2021. This research approach is quantitative research. This type of descriptive quantitative research. The nature of this research is descriptive explanatory research. The population in this study are customers who make purchases at PT. Surya Andalan Global Abadi, amounting to 370 customers, where for testing the validity and reliability used by the researcher were 30 customers and the rest were 192 customers as the sample test. The classical assumption tests used include: normality test, multicollinearity test, and heteroscedicity test. This data analysis model uses multiple regression analysis. The results of the study as well as the conclusion of the study is the product quality strategy of 3.034 with a significant value of 0.003 partially significant effect on purchasing decisions at PT. Surya Andalan Global Abadi. Packages of 3.060 with a significant value of 0.003 partially have a significant effect on purchasing decisions at PT. Surya Andalan Global Abadi. Service quality of 2,664 with a significant value of 0.008 partially influences customer purchasing decisions at PT. Surya Andalan Global Abadi.